Alcohol-mediated susceptibility to lung fibrosis is associated with group 2 innate lymphoid cells in mice - Chen, Liang; Sun, Rui; Lei, Chao; Xu, Zhishan; Song, Yong; Deng, Zhongbin (Frontiers in Immunology, 2023)
Chronic alcohol ingestion promotes acute lung injury and impairs immune function. However, the mechanisms involved are incompletely understood. Here, we show that alcohol feeding enhances bleomycin-induced lung fibrosis and inflammation via the regulation of type 2 innate immune responses, especially by group 2 innate lymphoid cells (ILC2s). Neuroimmune interactions have emerged as critical modulators of lung inflammation. We found alcohol consumption induced the accumulation of ILC2 and reduced the production of the neuropeptide calcitonin gene-related peptide (CGRP), primarily released from sensory nerves and pulmonary neuroendocrine cells (PNECs). CGRP potently suppressed alcohol-driven type 2 cytokine signals in vivo. Vagal ganglia TRPV1+ afferents mediated immunosuppression occurs through the release of CGRP. Inactivation of the TRPV1 receptor enhanced bleomycin-induced fibrosis. In addition, mice lacking the CGRP receptor had the increased lung inflammation and fibrosis and type 2 cytokine production as well as exaggerated responses to alcohol feeding. Together, these data indicate that alcohol consumption regulates the interaction of CGRP and ILC2, which is a critical contributor of lung inflammation and fibrosis.